ANALISA STRUKTUR HALF PIPE FENDER DENGAN VARIASI DESIGN PADA LAMBUNG KAPAL - Bagus Setiawan Permana; Akhmad Basuki Widodo (Fakultas Sains dan Teknologi Universitas Karimun, 2022)
In this research, we will explain about the design and analysis of ship fenders that can reduce damage to the hull structure when there is a collision between the ship and the pier. With the design of the ASTM A36 steel fender for a special study on KMP Nusa Dua using the finite element analysis method assisted by ANSYS software which is able to simulate the strength of the fender structure that we designed, from here we will get a fender design that is able to protect the hull structure when a contact occurs. collision between the ship and the dock. For the fender material data that will be used in the simulation through the ANSYS software is ASTM A36 Steel based on data from ASME which will then be given a load with the value of the ship's energy rating when leaning. The results of this simulation will get an analysis of the stress and deformation of the fenders on the hull and how well the fenders absorb the collision between the ship and the pier. Keywords: Ship Fender, Finite Elemen Analysis, Berthing Energy